ANALISIS PENERIMAAN MASYARAKAT TERHADAP PENGGUNAAN SISTEM AKSES LANGSUNG PELAYANAN DOKUMEN KEPENDUDUKAN CEPAT DAN AKURAT "ALPUKAT BETAWI" BERDASARKAN MODEL DELONE DAN MCLEAN - Nadya Ramadhani (2022)
E-government is one of the usage on information systems by government agencies in order to increase public satisfaction by services. The Dukcapil DKI Jakarta government agency has made an online population administration service innovation, namely the Akses Langsung Pelayanan Dokumen Kependudukan Cepat dan Akurat (ALPUKAT Betawi) application to facilitate the public in managing population administration. The Alpukat Betawi application is a new system and based on review data on the Playstore and Appstore in December 2021, in which not all people are satisfied and able to receive the Alpukat Betawi application service due to some problems. Therefore, this study has been conducted to determine the level of public acceptance of every aspect of the quality of the Alpukat Betawi application with test analysis using the relationship between the variables of the DeLone and Mclean information system success models. This research is a quantitative study with a total of 420 respondents in which the data processing and analysis method used the Structural Equation Model (SEM) by AMOS software. The results obtained are four of the nine hypotheses accepted with a positive and significant effect, namely the relationship between information quality and its usage, information quality by user satisfaction, usage by net benefits, and user satisfaction and net benefits, consequently, public acceptance of the Alpukat Betawi application usage is accepted but not good enough based on DeLone and McLean Model.